A-10s over Kosovo the victory of airpower over a fielded army as told by the airmen who fought in Operation Allied Force (Air Univ. Press, 2003)
Beretter om den amerikanske indsats med "Close Air Support"-flyet A-10 under "Operation Allied Force" over Kosovo og Serbien i 1999.